Ventricular repolarization is improved by His resynchronization therapy but not biventricular pacing. - Samways,JW; Cheng,T; Chow,J-J; Shun-Shin,MJ; Ali,N; Keene,D; Howard,JP; Naraen,A; Saleh,K; Kaza,N; Sharma,C; Mohal,JS; et al. (Heart Rhythm, 2026)
BACKGROUND: Biventricular pacing (BVP) delivered cardiac resynchronization therapy (CRT) modestly improves activation synchrony in patients with heart failure and left bundle branch block (LBBB) but can trigger ventricular arrhythmias. His bundle pacing (HBP) can correct LBBB as an alternative CRT method, producing superior ventricular activation synchrony and hemodynamics. OBJECTIVE: The aim of the study was to investigate the relative effects of HBP-CRT and BVP-CRT on ventricular repolarization. METHODS: Patients with LBBB referred for BVP-CRT underwent intra-procedural non-invasive epicardial mapping during atrial pacing (intrinsic LBBB), BVP-CRT, and temporary HBP. When HBP corrected LBBB, changes from baseline (LBBB) in overall and left ventricular (LV) repolarization dispersion (ΔVRT, ΔLVRT), repolarization gradient (ΔVRG, ΔLVRG) and activation-recovery interval (ARI) dispersion (ΔVARI, ΔLVARI) were measured. RESULTS: 17 patients had full datasets. BVP-CRT had no effect on global repolarization dispersion, gradient steepness or ARI (ΔVRT -1.5 ms, 95% confidence interval [CI] -15.4 to +12.4, P = .82; ΔVRG -0.00549 ms/mm, -0.106 to +0.0954, P = .9; ΔVARI -5.0 ms, -24.3 to +14.3, P = .59) and worsened the parameters in the LV (ΔLVRT +14.5 ms, +0.05 to +28.9, P = .049; ΔLVRG +0.0931 ms/mm, -0.0635 to +0.25, P = .226, ΔLVARI +28.6 ms, 95% CI +6.0 to +51.2, P = .02). HBP-CRT significantly improved global repolarization dispersion, gradient steepness and ARI (ΔLVRT +14.5 ms, +0.05 to +28.9, P = .049; ΔLVRG +0.0931 ms/mm, -0.0635 to +0.25, P = .226; ΔVARI -49.5 ms, -69.0 to -29.9, P < .0001) and within the LV (ΔLVRT -38.2 ms, -48.7 to -27.6, P < .001; ΔLVRG -0.228 ms/mm, -0.334 to -0.122, P = .0003; ΔLVARI -37.2 ms, -59.4 to -15.0, P = .003). CONCLUSION: HBP-CRT improves LBBB-induced repolarization abnormalities through improved activation synchrony and AR